A qualitative study of lived experiences of underrepresented electrical workers using creative non-fiction - Zhiyang Shi; Donia Obeidat; Ali Bani-Fatemi; Aaron Howe; Behdin Nowrouzi-Kia (PLoS ONE, 2026)
Objectives Women, Indigenous peoples, racialized individuals, and persons with disabilities remain underrepresented in the electrical industry. This study explored the lived experience of underrepresented electrical workers related to their mental health and workplace integration. Methods A qualitative narrative design was employed. One-on-one interviews were conducted with eleven participants who self-identified as women, Indigenous peoples, racialized individuals, and/or persons with disabilities. Interview data were first analyzed using a narrative thematic approach and informed the development of creative non-fictional stories. Results Three stories were developed. Story 1 – “Asking for a ride: being a women electrician” illustrated the experiences of a woman apprentice who faced inadequate job site accommodations and sexism challenges in the workplace. Story 2 – “The lunch talk: Indigenous people and racialized individuals in the trade” highlighted the experiences of Indigenous and racialized participants who encountered language barriers and discriminatory comments. Story 3 – “Luke’s notes: living and working with disability” demonstrated the impacts of physical disability on the daily work of electrical workers, particularly in managing the physical demands and mental health strains. Conclusions Electrical workers from underrepresented groups experience persistent barriers to mental health and workplace integration, including a lack of accommodations, limited social support, and experiences of discrimination at the workplace. These individuals also reported challenges in seeking workplace support due to a “toughness” culture within the industry. Electrical employers should foster an inclusive organizational culture that prioritizes the health and psychosocial well-being of underrepresented workers.